2020
DOI: 10.1111/all.14542
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic workup including CD203c‐based basophil activation test in immediate hypersensitivity due to metronidazole and ornidazole and evaluation of cross‐reactivity in between

Abstract: Background Little is known about the diagnostic approaches for immediate hypersensitivity reactions (IHRs) due to 5‐nitroimidazole antibiotics. The aim was to evaluate the usefulness of in vivo tests and basophil activation test (BAT) for the diagnosis of IHRs due to metronidazole and ornidazole and to determine possible cross‐reactivity in between. Methods Forty‐nine patients with a clear history of IHRs due to these drugs and 20 healthy subjects who were known to tolerate these drugs were included. Skin test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 50 publications
(101 reference statements)
0
8
0
Order By: Relevance
“…Sensitivity for penicillins ranges from 22% to 55% and for clavulanic acid up to 52.7%, both of them with a good specificity (79–96%) [ 28 , 68 , 69 , 70 , 71 ]. Moreover, recent studies have demonstrated that the basophil activation test is a promising technique, complementary to skin tests, for diagnosing allergy to amoxicillin–clavulanic acid [ 72 , 73 ], cefazolin (sensitivity rate up to 66.7%) [ 74 ] and 5-nitroimidazole (sensitivity rate up to 83.3%) [ 75 ].…”
Section: The Role Of In Vitro Tests In Antibiotic Allergy De-labelingmentioning
confidence: 99%
“…Sensitivity for penicillins ranges from 22% to 55% and for clavulanic acid up to 52.7%, both of them with a good specificity (79–96%) [ 28 , 68 , 69 , 70 , 71 ]. Moreover, recent studies have demonstrated that the basophil activation test is a promising technique, complementary to skin tests, for diagnosing allergy to amoxicillin–clavulanic acid [ 72 , 73 ], cefazolin (sensitivity rate up to 66.7%) [ 74 ] and 5-nitroimidazole (sensitivity rate up to 83.3%) [ 75 ].…”
Section: The Role Of In Vitro Tests In Antibiotic Allergy De-labelingmentioning
confidence: 99%
“…Moreover, two studies have demonstrated that BAT can be used as diagnostic tool for IHSRs to different groups of antibiotics, 5‐nitroimidazole and cefazolin, showing sensitivity rate up to 83.3% 3 and 66.7%, respectively 19 . In addition, BAT was able to diagnose patients allergic to quinolones, with a higher sensitivity than skin prick test (SPT) 20 .…”
Section: In Vitro Tools For the Diagnosis Of Hsr To Drugs What's New ...mentioning
confidence: 99%
“…In addition, prior known cellular tests for IHSR and NIHSR, such as basophil activation test (BAT), lymphocyte transformation test (LTT), enzyme‐linked ImmunoSpot (EliSpot), and T‐cells clonality have been deeply analysed and tuned up their techniques. 2 , 3 , 4 , 5 , 6 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another advantage of the BAT lies in its capacity to simultaneously and safely test different compounds, including products that are not intended for human use. This asset is particularly useful when exploring the absence or presence of cross-reactivity [60][61][62][63][64] , incrimination of (hidden) excipients [65][66][67][68] , identification of specific antigenic determinants or changes thereof 69,70 . For example, we used the BAT to demonstrate that the sugammadex-rocuronium inclusion complex (S-R-Cx) can be allergenic and is capable of triggering sIgE/FcεRI-dependent anaphylaxis due to a shape alteration involving the thio(carboxyethyl)sodium side chains attached at the primary rim of the host sugammadex molecule.…”
Section: Basophil Activation Tests In Immediate Drug Hypersensitivity...mentioning
confidence: 99%